2005
DOI: 10.1158/0008-5472.can-04-4017
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB–Dependent Mechanisms in Breast Cancer Cells Regulate Tumor Burden and Osteolysis in Bone

Abstract: A central mediator of a wide host of target genes, the nuclear factor-KB (NF-KB) family of transcription factors, has emerged as a molecular target in cancer and diseases associated with bone destruction. To evaluate how NF-KB signaling in tumor cells regulates processes associated with osteolytic bone tumor burden, we stably infected the boneseeking MDA-MB-231 breast cancer cell line with a dominant-negative mutant IKB that prevents phosphorylation of IKBa and associated nuclear translocation of NF-KB. Blocka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 56 publications
4
12
0
Order By: Relevance
“…Results from the histomorphometric analysis indicated that there was a significant reduction in trabecular bone area in the presence of MDA-MB-231 cells at 36 days post-injection and that the extent of bone loss increased with time; which supports the findings of previous studies [13,34] where a decrease in trabecular bone area was observed following intratibial implantation of MDA-MB-231 cells. Our results also indicate that significant evidence of bone loss only occurred following two bone remodelling cycles, given that there was no significant reduction in %Tb.Ar in the cancer-injected limb at 18 days post-injection.…”
Section: Discussionsupporting
confidence: 88%
“…Results from the histomorphometric analysis indicated that there was a significant reduction in trabecular bone area in the presence of MDA-MB-231 cells at 36 days post-injection and that the extent of bone loss increased with time; which supports the findings of previous studies [13,34] where a decrease in trabecular bone area was observed following intratibial implantation of MDA-MB-231 cells. Our results also indicate that significant evidence of bone loss only occurred following two bone remodelling cycles, given that there was no significant reduction in %Tb.Ar in the cancer-injected limb at 18 days post-injection.…”
Section: Discussionsupporting
confidence: 88%
“…The RANKL-RANK signaling axis is important at the tumorbone interface in the differentiation and activation of osteoclasts (3,9,(21)(22)(23)(24). Osteoclasts are major producers of MMP9 (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of NF-kB signaling in MDA-MB-231 cells by the mutant IkappaB decreased in vitro cell proliferation (Gordon and O'Keefe, 2005). Proliferation and activation of bronchial epithelial cells are also associated with activation of the NF-kB signal (Vignola and Chiappara, 2001).…”
Section: Induction Of Cell Growth and Inhibition Of Apoptosis In Humamentioning
confidence: 99%